Prevalence, Knowledge, Attitudes, and Perceptions About E-Cigarette Smoking Among Students in the Dental Fields in Jordan - Suhair R. Obeidat; Zain A. Malkawi; Omar F. Khabour; Amani Gh. AlSa’di (International Journal of Dentistry)
Conclusions: The prevalence of e-cigarette smoking among dental students in Jordan is high and necessitates health education programs to increase awareness of the associated health risks among young adults, specifically in educational settings.